The Effect of Cocamide Dea on the Characteristics of Ginger and Celery Extract Shampoo Preparations - Anastasia, Desy Siska; Septiani, Rahmi; Isnindar, Isnindar (Majalah Obat Tradisional, 2024)
Ginger and celery extracts are recognized anti-dandruff agents. Managing dandruff can be accomplished by creating a cleanser formulation. Shampoo contains an essential cleansing ingredient known as surfactant. SLS enables good foams, but at >10% concentration, it irritates skin. Adding a nonionic surfactant like cocamide DEA reduces irritation. This study examined how cocamide DEA concentrations affected the physical qualities and hedonic evaluation of a shampoo containing ginger and celery extracts. The shampoo was produced in three formulas with differing cocamide DEA concentrations: F1 (6%), F2 (8%), and F3 (10%). The formulation is evaluated using organoleptic, homogeneity, viscosity, pH, bulk density, foam height, foam stability, cycling, hedonic, and irritant studies. The result of this study revealed that shampoo had a brownish-orange color, a ginger-mint scent, and different looks. All three formulations were homogeneous, did not separate during cycling, and had significant viscosity variances, pH, bulk density, foam height, and foam stability. The formula with an 8% cocamide DEA concentration was the most popular and did not produce irritation. In conclusion, varying cocamide DEA concentrations affect the physical properties and preferences of panelists in a shampoo formulation that includes ginger and celery extracts.